Neuroblastoma in early childhood: A rare case report and review of literature - Ritesh R Kalaskar; Ashita R Kalaskar (Wolters Kluwer Medknow Publications, 2016)
Neuroblastoma is an extremely rare pediatric neoplasm whose prognosis becomes poor and poor as the age advances. It can be sporadic or nonfamilial in origin. It is primarily a tumor of abdominal origin from where it metastasis to lymph nodes, liver, intracranial and orbital sites, and central nervous system. There is no standard dental treatment protocol for the management of neuroblastoma due to its poor survival rate and rarity. However, dental treatment may follow the protocol of preventive and restorative. Surgicals should be performed under supervision as it may trigger metastasis. We report a rare case of neuroblastoma in a 3-year-old child presenting classical oral manifestations such as bilateral palatal swelling, rolled border ulcer on the posterior part of hard palate adjacent to primary molars, and bilateral proptosis.